Exploring EPR Parameters of 99Tc Complexes for Designing New MRI Probes: Coordination Environment, Solvent, and Thermal Effects on the Spectroscopic Properties. (14th June 2017) - Pereira, Bruna T. L.; Silva, Érika Ferreira; Gonçalves, Mateus A.; Mancini, Daiana T.; Ramalho, Teodorico C.
Abstract : We have evaluated the solvent and thermal effects on spectroscopic parameters of 99 Tc complexes coordinated to explicit water molecules. Molecular dynamics simulations were performed followed by hyperfine coupling constant calculations (A i s o ). Our results show a significant increase of A i s o, which demonstrates that the studied compounds can be promising contrast agents in MRI.